The Role of Occupational Medicine, Nursing and Radiology in Diagnosis and Managing Work-Related Injuries - Dr. Afaf M. Alshanqiti; Ammash Ageel Alshammari; Naif Hawsh Saleh Alonazi; Abdulrahman Hamed Oudah Alharbi; Rakan Menwer Lafi Alharbi; Sultanah Mufrah Alenazi; Riyadh Abdulaziz Saleh Alanazi; Ali Radhi Nazzal Alshammari; Sultan Essa Ayyadah Alshammari; Bunder Hamed Muqbel Alshammari; Fahad Shayhan Mohammed Alshammari; Manal Ali Hassan Algharbi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Occupational medicine physicians, nurses, and radiologists all work together in the diagnosis, management, and prevention of occupational injuries. Each of them provides vital pieces in a collaborative, multidisciplinary approach to ensure that safer work environments are created and support the rehabilitation of injured workers. The occupational medicine physicians spearhead injury assessment and prevention; the frontline caregivers who provide initial treatment and education are the nurses. The radiologists make crucial imaging diagnostics that provide guidance in the development of treatment plans. This paper explores the roles of these professionals in the management of work-related injuries and how collaboration and prevention efforts can be enhanced at the workplace.